Examining the complementarity between the ERIC compilation of implementation strategies and the behaviour change technique taxonomy: a qualitative analysis - McHugh, Sheena; Presseau, Justin; Luecking, Courtney T.; Powell, Byron J. (Implementation science : IS, 2022)
Background Efforts to generate evidence for implementation strategies are frustrated by insufficient description. The Expert Recommendations for Implementing Change (ERIC) compilation names and defines implementation strategies; however, further work is needed to describe the actions involved. One potentially complementary taxonomy is the behaviour change techniques (BCT) taxonomy. We aimed to examine the extent and nature of the overlap between these taxonomies. Methods Definitions and descriptions of 73 strategies in the ERIC compilation were analysed. First, each description was deductively coded using the BCT taxonomy. Second, a typology was developed to categorise the extent of overlap between ERIC strategies and BCTs. Third, three implementation scientists independently rated their level of agreement with the categorisation and BCT coding. Finally, discrepancies were settled through online consensus discussions. Additional patterns of complementarity between ERIC strategies and BCTs were labelled thematically. Descriptive statistics summarise the frequency of coded BCTs and the number of strategies mapped to each of the categories of the typology. Results Across the 73 strategies, 41/93 BCTs (44%) were coded, with ‘restructuring the social environment’ as the most frequently coded ( n =18 strategies, 25%). There was direct overlap between one strategy ( change physical structure and equipment ) and one BCT (‘restructuring physical environment’). Most strategy descriptions ( n =64) had BCTs that were clearly indicated ( n =18), and others where BCTs were probable but not explicitly described ( n =31) or indicated multiple types of overlap ( n =15). For some strategies, the presence of additional BCTs was dependent on the form of delivery. Some strategies served as examples of broad BCTs operationalised for implementation. For eight strategies, there were no BCTs indicated, or they did not appear to focus on changing behaviour. These strategies reflected preparatory stages and targeted collective cognition at the system level rather than behaviour change at the service delivery level. Conclusions This study demonstrates how the ERIC compilation and BCT taxonomy can be integrated to specify active ingredients, providing an opportunity to better understand mechanisms of action. Our results highlight complementarity rather than redundancy. More efforts to integrate these or other taxonomies will aid strategy developers and build links between existing silos in implementation science.